Exploring Elementary Students' Power and Solidarity Relations in an EFL Classroom - Tatiana Méndez; Andrea García (Universidad Nacional de Colombia, 2012)
This article derives from a critical discourse analysis study that reports the characteristics of elementary school students' power and solidarity relations in English as a foreign language classroom in Bogotá, Colombia, while we were doing our teaching English as a foreign language practicum. The study was based on theories of power and solidarity. The findings suggest that there are different forms of exercising power and solidarity in the classroom. Power can be resisted, challenged, or exercised by means of reproaches. Solidarity can take the form of taking sides to protect friends. These findings allow us to be aware of the complexities of the English language class.